Genome sequence of idiomarina sp strain a28l, isolated from pangong lake, india - Gupta, Hemant Kumar; Singh, Ajit; Sharma, Rakesh (Journal of Bacteriology, 2011)
Idiomarina sp. strain A28L was isolated from the alkaline brackish water of a high-altitude lake, Pangong Lake. Here, we present the draft genome of Idiomarina sp. strain A28L, which contains 2,591,567 bp with a G + C content of 45.5 mol% and contains 2,299 protein-coding genes and 56 structural RNAs.

Genome sequence of rheinheimera sp strain A13L, isolated from pangong lake, india - Gupta, Hemant Kumar; Gupta, Rinkoo Devi; Singh, Ajit; Chauhan, Nar Singh; Sharma, Rakesh (Journal of Bacteriology, 2011)
Rheinheimera sp. strain A13L, which has antimicrobial activity, was isolated from alkaline brackish water of the high-altitude Pangong Lake of Ladakh, India. Here we report the draft genome sequence of Rhienheimera sp. strain A13L (4,523,491 bp with a G + C content of 46.23%). The genome is predicted to contain genes for marinocine and colicin V production, which may be responsible for the antimicrobial activity of the strain.

Genome sequence of nitratireductor aquibiodomus strain RA22 - Singh, Ajit; Jangir, Pramod Kumar; Kumari, Chanchal; Sharma, Rakesh (Journal of Bacteriology, 2012)
The genus Nitratireductor represents nitrate-reducing bacteria from the family Phyllobacteriaceae. Here we report the draft genome sequence of Nitratireductor aquibiodomus strain RA22, which contains 4,592,790 bp, with a G+C content of 61.30%, and has 4,241 protein coding genes.

Genome sequence of the alkaliphilic bacterium nitritalea halalkaliphila type strain LW7, isolated from Lonar Lake, India - Jangir, Pramod Kumar; Singh, Ajit; Shivaji, S.; Sharma, Rakesh (Journal of Bacteriology, 2012)
An alkaliphilic bacterium, Nitritalea halalkaliphila LW7, which belongs to the family Cyclobacteriacae in the phylum Bacteroidetes, was isolated from Lonar Lake in Maharastra, India. Here we announce the draft genome sequence of the type strain LW7, which contains 3,633,701 bp with a G+C content of 48.58%.